TEACHING METHODS OF LEARNING STYLES TO VISUAL ADULT LEARNERS - Ibragimova Dilafruz Shukhratovna; Muhammadjonova Bibikhonim Adhamjon kizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
The problem of adapting teaching techniques for foreign languages to the learning styles of students seems especially pertinent in the current educational context of updating the educational process to boost training efficacy. The learning styles that educators, trainers, and researchers have developed can be categorized in a wide variety of ways. Finding your preferred learning style will help you make the most of the related strategies to maximize the learning potential of your coursework. This article focus on teaching methods for adult learners with visual learning styles and adult learners' essential learning styles and how to support them in learning.